External validation of a novel signature of illness in continuous cardiorespiratory monitoring to detect early respiratory deterioration of ICU patients. (27th September 2021) - Callcut, Rachael A; Xu, Yuan; Moorman, J Randall; Tsai, Christina; Villaroman, Andrea; Robles, Anamaria J; Lake, Douglas E; Hu, Xiao; Clark, Matthew T
Abstract: Objective: The goal of predictive analytics monitoring is the early detection of patients at high risk of subacute potentially catastrophic illnesses. An excellent example of a targeted illness is respiratory failure leading to urgent unplanned intubation, where early detection might lead to interventions that improve patient outcomes. Previously, we identified signatures of this illness in the continuous cardiorespiratory monitoring data of intensive care unit (ICU) patients and devised algorithms to identify patients at rising risk. Here, we externally validated three logistic regression models to estimate the risk of emergency intubation developed in Medical and Surgical ICUs at the University of Virginia. Approach: We calculated the model outputs for more than 8000 patients in the University of California—San Francisco ICUs, 240 of whom underwent emergency intubation as determined by individual chart review. Main results: We found that the AUC of the models exceeded 0.75 in this external population, and that the risk rose appreciably over the 12 h before the event. Significance: We conclude that there are generalizable physiological signatures of impending respiratory failure in the continuous cardiorespiratory monitoring data.